2016
DOI: 10.1089/sur.2015.213
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Not Associated with Antimicrobial Treatment Failure for Intra-Abdominal Infection

Abstract: Background: Obesity and commonly associated comorbidities are known risk factors for the development of infections. However, the intensity and duration of antimicrobial treatment are rarely conditioned on body mass index (BMI). In particular, the influence of obesity on failure of antimicrobial treatment for intra-abdominal infection (IAI) remains unknown. We hypothesized that obesity is associated with recurrent infectious complications in patients treated for IAI. Methods: Five hundred eighteen patients rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…As of yet, however, there are little data documenting improvements in clinical outcomes with use of these alternative dosing strategies. In fact, obesity has not been uniformly identified as a significant risk factor for an adverse outcome in patients with IAI [574,575], Continuous or prolonged (over 3-4 h) antibiotic infusion, as opposed to intermittent infusion (over 30-60 min), is a therapeutic tactic designed to take advantage of the pharmacokinetic and pharmacodynamic properties of specific antibiotic agents to maximize their clinical efficacy. The primary class of antibiotic agents that has been assessed using continuous or prolonged infusion are b-lactams.…”
Section: Agentmentioning
confidence: 99%
“…As of yet, however, there are little data documenting improvements in clinical outcomes with use of these alternative dosing strategies. In fact, obesity has not been uniformly identified as a significant risk factor for an adverse outcome in patients with IAI [574,575], Continuous or prolonged (over 3-4 h) antibiotic infusion, as opposed to intermittent infusion (over 30-60 min), is a therapeutic tactic designed to take advantage of the pharmacokinetic and pharmacodynamic properties of specific antibiotic agents to maximize their clinical efficacy. The primary class of antibiotic agents that has been assessed using continuous or prolonged infusion are b-lactams.…”
Section: Agentmentioning
confidence: 99%
“…The STOP-IT study showed that obesity is not associated with antimicrobial treatment failure among patients with IAIs. This suggests that obesity may not independently influence the need for longer duration of antimicrobial therapy in treatment of IAI compared to non-obese patients [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, standard AMP doses provide lower antibiotic concentrations per kilogram in overweight and obese patients compared with patients of normal bodyweight. Still, the results of a number of studies 25–28 including between 25 and 500 patients appear to have indicated that a standard AMP dose is sufficient to prevent SSI, even in obese patients. Possibly based on these reports, weight-adjusted AMP dosing is still debated 1–4 .…”
Section: Discussionmentioning
confidence: 99%
“…However, dosing guidelines for antibiotics most frequently used in AMP do not recommend weight-based dose adjustments 1 , 4 , 22 because the use of standardized doses is considered safe, effective, and convenient for most of the adult patient population 1 . Although double-dose AMP administration has been suggested for morbidly obese patients weighing at least 120 kg, or with a BMI of 40 kg/m 2 or higher 22–24 , studies 25–28 involving relatively small numbers of patients appear to suggest that standard AMP doses do successfully prevent SSI even in obese patients. Therefore, according to Centers for Disease Control and Prevention (CDC) guidelines for SSI prevention, the issue of weight-adjusted AMP dosing is still considered unresolved 1 , 4 .…”
Section: Introductionmentioning
confidence: 99%